2016
DOI: 10.1016/j.apcatb.2015.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of TiO2 polycrystalline sub-micron fibers with variable rutile fraction

Abstract: TiO 2 polycrystalline sub-micron fibers can be used as photocatalysts for the degradation of a variety of organic molecules. Here we report on the optimization of these fibers for decontaminating pharmaceutical agents in aqueous medical waste streams. Mixed-phase TiO 2 fibers have been prepared via a sol-gel technique followed by electrospinning and calcination. By adjusting the calcination temperature, the rutile phase fraction in TiO 2 fibers can be tuned relative to the anatase phase from 0% to 100%. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…TiO 2 fibers were prepared by a using a sol-gel synthesis, followed by electrospinning of polymer sol-gel, and calcination treatment of polymer fibers as shown in Scheme 1. 17,19,20 A polymeric sol-gel was generated by stirring and ambient hydrolysis of TTIP using 1:2 mass ratio of PMMA:TTIP, where 320 mg of PMMA (MW = 35,000 g/mol) was completely dissolved in 2 mL of chloroform followed by drop wise addition of 640 mg of TTIP with continuous stirring for 30 min. 2 mL of DMF was then added and stirred for 2 h to increase the dielectric constant of the composite solution which aids in the electrospinning process.…”
Section: Synthesis Of Tio 2 Electrospun Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 fibers were prepared by a using a sol-gel synthesis, followed by electrospinning of polymer sol-gel, and calcination treatment of polymer fibers as shown in Scheme 1. 17,19,20 A polymeric sol-gel was generated by stirring and ambient hydrolysis of TTIP using 1:2 mass ratio of PMMA:TTIP, where 320 mg of PMMA (MW = 35,000 g/mol) was completely dissolved in 2 mL of chloroform followed by drop wise addition of 640 mg of TTIP with continuous stirring for 30 min. 2 mL of DMF was then added and stirred for 2 h to increase the dielectric constant of the composite solution which aids in the electrospinning process.…”
Section: Synthesis Of Tio 2 Electrospun Fibersmentioning
confidence: 99%
“…Prior studies have shown that excited electrons in the conduction band favor the formation of peroxide radical anions in the presence of adsorbed oxygen on the surface. 17 The generation of these radicals in the presence of visible light is expected to improve the effectiveness of the catalyst, increasing the rate of PAP degradation. Fisher.…”
Section: Introductionmentioning
confidence: 99%
“…The Zr–OH–Zr structure of UiO‐66 plays a role similar to that of the Zn–OH–Zn active site in the phosphotriesterase enzyme . Based on these reports, many researchers have tried to apply UiO series MOFs including UiO‐66 for the decomposition of the phosphate ester‐based nerve agents VX, soman and distilled mustard . Some of these approaches involve nanofiber formation via electrospinning using ligand‐modified UiO‐66 or TiO 2 nanoparticles to accelerate the hydrolysis reaction by UiO‐66 …”
Section: Introductionmentioning
confidence: 99%
“…The typical procedures to fabricate VPP PEDOT/TiO composite sub-micron fibers are shown in Figure 1. TiO 2 fibers were obtained through electrospinning and calcination following a previously described method [37]. To prepare the polymeric sol-gel used for electrospinning, 320 mg PMMA was dissolved in 2 mL chloroform and then 640 mg TTIP was added dropwise.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous and smooth polymer fibers were pulled out by 25 kV voltage provided by the external power supply and collected with the Al foil collector which was 18 cm away from the tip of the syringe. The collected polymer fibers were placed under ambient conditions to achieve full hydrolysis and further condensation to amorphous TiO 2 [37]. The calcination treatment was carried out in air at 450, 550 or 700 °C for 4 hours to control the TiO 2 polymorph composition.…”
Section: Introductionmentioning
confidence: 99%